2015
DOI: 10.1158/2326-6066.cir-15-0077-t
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibition Upregulates PD-1 Ligands in Melanoma and Augments Immunotherapy with PD-1 Blockade

Abstract: Expression of PD-1 ligands by tumors and interaction with PD-1 expressing T cells in the tumor microenvironment can result in tolerance. Therapies targeting this co-inhibitory axis have proven clinically successful in the treatment of metastatic melanoma, non-small cell lung cancer and other malignancies. Therapeutic agents targeting the epigenetic regulatory family of histone deacetylases (HDACs) have shown clinical success in the treatment of some hematologic malignancies. Beyond direct tumor cell cytotoxici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
305
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(333 citation statements)
references
References 44 publications
11
305
2
Order By: Relevance
“…A previous study demonstrated PD-L1 elevation in melanoma cell lines and patient melanoma biopsies after entinostat treatment. 24 Here we demonstrate that HDAC inhibition elevates PD-L1 levels across diverse carcinoma cell types in vitro and in human prostate and NSCL cancer xenografts (Table 1, Figure 1). Normally, this would be considered a disadvantageous effect of HDAC inhibition because PD-L1 is involved in promoting tolerance and decreasing immune surveillance.…”
Section: Discussionmentioning
confidence: 56%
“…A previous study demonstrated PD-L1 elevation in melanoma cell lines and patient melanoma biopsies after entinostat treatment. 24 Here we demonstrate that HDAC inhibition elevates PD-L1 levels across diverse carcinoma cell types in vitro and in human prostate and NSCL cancer xenografts (Table 1, Figure 1). Normally, this would be considered a disadvantageous effect of HDAC inhibition because PD-L1 is involved in promoting tolerance and decreasing immune surveillance.…”
Section: Discussionmentioning
confidence: 56%
“…In particular, class I HDAC inhibition causes upregulation of PD-L1, and PD-L2 to a less extent, in human and murine cell lines in vitro. This was confirmed in vivo in a murine cell melanoma model where mice, receiving a combination treatment with HDACi panobinostat and an anti-PD-1, showed slower tumor progression and increased survival [105]. However, as seen with other signaling pathways, HDAC i nhibition may be tissue and HDAC specific.…”
Section: Hdaci and Immune Checkpoints Inhibitorsmentioning
confidence: 70%
“…Preclinical studies suggest that the upregulation of immune checkpoints is epigenetically regulated through the action of HDACi that modulate PD-L1 expression in melanoma [104,105]. In particular, class I HDAC inhibition causes upregulation of PD-L1, and PD-L2 to a less extent, in human and murine cell lines in vitro.…”
Section: Hdaci and Immune Checkpoints Inhibitorsmentioning
confidence: 99%
“…Further evidence of epigenetically regulated PD-L1 expression is provided by studies using HDAC inhibitors in melanoma cell lines. Specifically, treatment with class I HDAC inhibitors resulted in increased acetylation of histone 3 in PD-L1 and PD-L2 promoter regions, which resulted in increased PD-L1 expression in vitro and in vivo [104].…”
Section: Epigenetic Alterations and Immunotherapymentioning
confidence: 99%